Role of the endocytic recycling pathway in lysosome exocytosis - Lopes, Liliana Manuela Bento (2019)
Until recently, lysosomes were considered as the end-point of the endocytic pathway, to where cargo is delivered to be degraded. However, several studies showed that conventional lysosomes can undergo regulated exocytosis in response to an increase in intracellular calcium concentration, an important process for plasma membrane repair and secretion of lysosomal contents. Nevertheless, the molecular machinery involved in lysosome transport and fusion with the plasma membrane is not fully understood. Our group found recently that the small GTPases Rab11a and Rab11b are essential for calcium-triggered lysosome exocytosis in HeLa cells. Therefore, we aim to find the Rab11a/b effectors that mediate lysosome exocytosis process. To this end, we silenced several known effectors such as Rab11 family of interacting proteins (FIPs), Myosin Va/b or subunits of the exocyst tethering complex (Sec8, Sec15 and Exo70). After stimulation with the calcium ionophore ionomycin, we investigated the cell surface expression levels of the late endosome/lysosome marker LAMP1, as well as the release of the lysosomal enzyme β-hexosaminidase. We found that the silencing of Sec15 impairs lysosome exocytosis, while in the absence of FIP1-C or FIP2 there is an increase in LAMP1 cell surface levels and β-hexosaminidase release. Moreover, we confirmed the interaction and co-localization of Rab11a/b with the effector proteins studied using co-immunoprecipitation assays and confocal immunofluorescence microscopy, respectively. Finally, using live cell imaging, we found that Rab11-positive vesicles interact transiently with late endosomes/lysosomes near the plasma membrane, upon ionomycin stimulation. Thus, our results provide new insights into the role of Rab11 and its effectors in the regulation of conventional lysosome exocytosis.